Estudio del comportamiento organizacional en la cooperativa de ahorro y crédito Chone Ltda. - Alcívar Mendoza, Christian Antonio (2019)
The purpose of this research was to study the organizational behavior in the credit and savings cooperative Chone Ltda., For the contribution in the management decisions, for this three phases were carried out, which were to identify and evaluate the organizational behavior variables and propose an improvement plan, in the first phase allowed the determination of the team of experts, the variables for the study of organizational behavior in the savings and credit cooperative Chone Ltda. were identified, thus evaluating the variables: communication, motivation , leadership and teamwork, the same that provided a general diagnosis to know the current state of the work environment and the internal environment of said financial institution, in the second phase an evaluation of the variables of organizational behavior was carried out through the survey it was possible to identify that the factors that have the greatest impact on The residence between employees and executives of the institution is the lack of internal communication, as well as the low motivation given to employees in matters of improvement, which therefore affects the performance and performance of the organization, in the last In this phase, an improvement plan was carried out, which is aimed at optimizing and strengthening the variables of organizational behavior in said financial institution, which will have as its main function to improve the work environment in matters of communication and motivation, thus offering alternatives of solution in a certain period of time.